2018
DOI: 10.1108/ijlss-11-2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Six Sigma project: a comparative study of DEA and LDA techniques

Abstract: Purpose Nowadays, most of the organizations have focused through the world on Six Sigma to reduce the costs, improve the productivity and enhance concerned individuals’ satisfaction, especially customers’ satisfaction. Annually, these organizations define and execute thousands of Six Sigma projects which involve a great deal of investments. But are all of these projects successful and do the organizations benefit from the above advantages? The purpose of this study is to proposing a methodology to to answer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…As part of a systemic approach to improving performance, selecting the right project is important for a successful LSS implementation (Holmes et al , 2015; Sony et al , 2020; Sreedharan et al , 2019). Also, a strong analysis is required before the project initiation to minimize the risks that can occur during project execution (Hadi-Vencheh and Yousefi, 2018; Usman Tariq, 2013). To improve our understanding of the project selection process the following questions were asked, after asking them to recollect their most recent LSS project:…”
Section: Resultsmentioning
confidence: 99%
“…As part of a systemic approach to improving performance, selecting the right project is important for a successful LSS implementation (Holmes et al , 2015; Sony et al , 2020; Sreedharan et al , 2019). Also, a strong analysis is required before the project initiation to minimize the risks that can occur during project execution (Hadi-Vencheh and Yousefi, 2018; Usman Tariq, 2013). To improve our understanding of the project selection process the following questions were asked, after asking them to recollect their most recent LSS project:…”
Section: Resultsmentioning
confidence: 99%
“…Often, top management selects and prioritizes PI projects rather than functional experts who understand the exact deficiencies that need improvement (Iyede et al , 2018). To ensure that the right project is selected, specific guidelines and criteria should be established to enhance the benefits obtained from PI projects and satisfy organizational needs and objectives (Flifel et al , 2017; Hadi-Vencheh and Yousefi, 2018).…”
Section: Process Improvement Project Critical Failure Factorsmentioning
confidence: 99%
“…However, some research can be found which applied DEA for selecting, improving, or evaluating six sigma projects as well. For example, Hadi-Vencheh and Yousefi [26] and Wen et al [27] applied a hybrid DEA technique to select six sigma projects whereas Azadeh et al [28] performed a PCA-DEA approach to investigate the effect of six sigma extension on key job features in car industry.…”
Section: Literature Reviewmentioning
confidence: 99%